The Effect of Leadership and Work Motivation on Employee Performance at Basarnas, Pangkal Pinang City, with Job Satisfaction as an Intervening Variable - Danang Budi Prasetya; Suhardi Suhardi; Rahmad Firdaus (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of leadership and work motivation on employee performance, with job satisfaction as an intervening variable at Basarnas Pangkal Pinang City. This research employs a quantitative approach with an explanatory design. The population consists of 57 employees, all of whom were used as respondents through a census technique. Data were collected using a questionnaire with a five-point Likert scale, while data analysis was conducted using multiple linear regression and path analysis with the assistance of SPSS. The results show that leadership and work motivation have a positive and significant effect on job satisfaction. In addition, leadership, work motivation, and job satisfaction also have a positive and significant effect on employee performance. Job satisfaction is proven to have the most dominant influence on employee performance. The path analysis results indicate that job satisfaction acts as an intervening variable that mediates the relationship between leadership and work motivation on employee performance, both directly and indirectly. These findings indicate that improving employee performance in organizations with high-risk work environments such as Basarnas does not solely depend on structural aspects but also on employees’ psychological factors. Therefore, strengthening adaptive leadership and enhancing work motivation should be balanced with efforts to improve job satisfaction in order to achieve optimal performance. This study provides theoretical contributions to the development of organizational behavior models and practical implications for human resource management in the public sector, particularly in rescue institutions.